Xenopus pitx3 target genes lhx1 and xnr5 are identified using a novel three‐fluor flow cytometry–based analysis of promoter activation and repression. Issue 9 (13th July 2017) - Hooker, Lara N.; Smoczer, Cristine; Abbott, Samuel; Fakhereddin, Mohamad; Hudson, John W.; Crawford, Michael J.
Abstract : Background : Pitx3 plays a well understood role in directing development of lens, muscle fiber, and dopaminergic neurons; however, in Xenopus laevis, it may also play a role in early gastrulation and somitogenesis. Potential downstream targets of pitx3 possess multiple binding motifs that would not be readily accessible by conventional promoter analysis.Results: We isolated and characterized pitx3 target genes lhx1 and xnr5 using a novel three‐fluor flow cytometry tool that was designed to dissect promoters with multiple binding sites for the same transcription factor. This approach was calibrated using a known pitx3 target gene, Tyrosine hydroxylase .Conclusions: We demonstrate how flow cytometry can be used to detect gene regulatory changes with exquisite precision on a cell‐by‐cell basis, and establish that in HEK293 cells, pitx3 directly activates lhx1 and represses xnr5 . Developmental Dynamics 246:657–669, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: A novel flow cytometry-based method is deployed to characterize enhancer/promoter function on a cell-by-cell basis. The method is validated using a known gene target of pitx3, tyrosine hydroxylase. Pitx3, which expresses during Xenopus gastrulation, helps to regulate xnr5 and lhx1. Previously described somitogenesis anomalies induced by pitx3 knockdown are explicable by regulatory effects upon lhx1. Previously described pitx3-induced laterality defects are explicable by regulatory effects upon xnr5 which in turn acts upstream of xnr1, lefty, and pitx2.